Unwinding the mechanism of macrophage repolarization potential of Oceanimonas sp. BPMS22-derived protein protease inhibitor through Toll-like receptor 4 against experimental visceral leishmaniasis - Jayaraman, Adithyan; Srinivasan, Sujatha; Uppuluri, Kiran Babu; Kar Mahapatra, Santanu (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract: Oceanimonas sp. BPMS22-derived protein protease inhibitor (PPI) has proven to shift macrophages towards an inflammatory state and reduce Leishmania donovani infection in vitro and in vivo. The current study explored and validated mechanistic aspects of PPI and toll-like receptor (TLR) interaction. PPI exhibited the upregulation of TLR 2, 4 and 6 during treatment which was proven to orchestrate parasite clearance effectively. In silico study confirmed the high interaction with TLR4 and PPI. Immune blot confirmed the significant upregulation of TLR4 in macrophages irrespective of L. donovani infection. Pharmacological inhibition and immune blot study confirmed the involvement of PPI in TLR4-mediated phosphorylation of p38 MAPK and dephosphorylation of ERK1/2, repolarizing to pro-inflammatory macrophage state against experimental Visceral Leishmaniasis. In addition, in TLR4 knockdown condition, PPI treatment failed to diminish M2 phenotypical markers (CD68, Fizz1, Ym1, CD206, and MSR-2) and anti-inflammatory cytokines (IL-4, IL-10, and TGF-β). Simultaneously, PPI failed to upregulate the M1 phenotypical markers and pro-inflammatory cytokines (IL-1β, IL-6, IL-12, and IFN-γ) (p<0.001) during the TLR4 knockdown condition. In the absence of TLR4, PPI also failed to reduce parasite load, T cell proliferation, and impaired delayed-type hypersensitivity (DTH) response. The absence of pro-inflammatory cytokines was observed during a co-culture study with PPI-treated macrophages (in the TLR4 knockdown condition) with Day10 T-cell obtained from L. donovani-infected mice. This study supports the immunotherapeutic potential of PPI, as it interacted with TLR4 and promoted macrophage repolarization (M2-M1) to restrict the L. donovani parasite burden and helps in the mounting immune response against experimental Visceral Leishmaniasis.